Effectiveness and Benefits of Service Learning: Perceptions of Undergraduate Students in Sarawak - Nicholas, Gani (Universiti Malaysia Sabah, 2025)
Service learning is a pedagogical approach that has been applied in educational institutions worldwide since the 1970s. Beginning 2019, service learning has been implemented under the name ‘Service Learning Malaysia – University for Society’ (or SULAM) in the Malaysian university curriculum, including in Universiti Malaysia Sarawak (UNIMAS). However, in general, there has been lack of research regarding the effectiveness of service learning. This paper examines UNIMAS students’ perceptions of service learning projects. It describes the results of a study conducted among 83 second year Anthropology and Sociology students to investigate the effectiveness of service learning at the university level in Malaysia. The contents of the students’ reflection papers form the qualitative data of this study, which were analysed thematically using the inductive approach. The findings of this study indicate that most students perceive service learning to be effective in that their service learning projects have mainly achieved their goals. Furthermore, there were benefits gained by both students and the community through participation in service learning activities. This study adds to the growing body of knowledge on the efficacy of service learning, and the result show that service learning should continue to be implemented in the Malaysian academic curriculum. Additionally, this research helps to fill a notable void in studies examining the effectiveness and impacts of service learning in the Malaysian university context, particularly in Sarawak.